Photosynthetic Conversion of Carbon Dioxide to Oleochemicals by Cyanobacteria: Recent Advances and Future Perspectives - Wang, Li; Chen, Liyuan; Yang, Shihui; Tan, Xiaoming (Frontiers in Microbiology, 2020)
Sustainable production of biofuels and biochemicals has been broadly accepted as a solution to abate carbon dioxide emissions. Besides being used as lubricants or detergents, oleochemicals are attractive biofuels as they are compatible with existing transport infrastructures. Cyanobacteria are autotrophic prokaryotes possessing photosynthetic abilities with mature genetic manipulation systems. Through the introduction of exogenous or the modification of intrinsic metabolic pathways, cyanobacteria have been engineered to produce various bio-chemicals and biofuels in the recent decade. In this review, we specifically summarize recent progress on photosynthetic production of fatty acids, fatty alcohols, fatty alk(a/e)nes, and fatty acid esters by genetically engineered cyanobacteria. We also summarize recent reports on fatty acid and lipid metabolisms of cyanobacteria, and provide perspectives for economic cyanobacterial oleochemical production in the future.